A 56-year-old woman with early acute pulmonary emboli following pelvic reconstructive surgery. (23rd February 2011) - Jantzie, Lindsay; Lazare, Darren; Schulz, Jane; Flood, Cathy
Abstract : Venous thromboembolism (VTE) remains a significant cause of postoperative morbidity and mortality. There are few reports on acute symptomatic pulmonary embolism (PE) following urogynaecological surgery. The authors report a case of an adult woman who developed a massive acute PE early on postoperative day 1 following a complex reconstructive surgery. Following anticoagulation treatment and placement of an inferior vena cava filter, the patient recovered and was discharged without discomfort on the ninth postoperative day. While recognition of the early occurrence of VTE is important to ensure optimal patient care following major pelvic surgery, this case highlights the need to reconsider VTE prophylaxis protocols in moderate to high-risk populations undergoing elective surgery.